CLINICOPATHOLOGICAL AND BIOCHEMICAL CORRELATES OF CARBAPENEM-RESISTANT ENTEROBACTERIACEAE INFECTIONS AND THEIR ASSOCIATION WITH ORAL MICROBIOTA DYSBIOSIS AND SLEEP DISORDERS IN HOSPITALIZED PATIENTS - HINA FAISAL, ASIFA AFZAL, MARIUM TARIQ, SAEEDA ITRATH BATOOL, USHBA JAMAL, AMIR AKBAR SHAIKH (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Carbapenem-resistant Enterobacteriaceae (CRE) have emerged as a major public health concern due to their extensive drug resistance and association with prolonged hospital stays and increased mortality. Recent evidence suggests that systemic infections and microbial dysbiosis may influence both host immunity and sleep regulation, yet the interplay between CRE infections, oral microbiota alterations, and sleep disorders remains poorly understood. Objective: This study aims to explore the clinicopathological and biochemical characteristics of hospitalized patients with CRE infections and to examine their association with oral microbiota dysbiosis and sleep disturbances. Methods: A cross-sectional analytical study was conducted among hospitalized patients with laboratory-confirmed CRE infections. Clinical and biochemical profiles were obtained through medical records and laboratory investigations. Oral swabs were analyzed using culture and molecular methods to assess microbiota composition. Sleep quality was evaluated through standardized questionnaires and clinical assessment. Correlation analyses were performed to identify associations between infection severity, biochemical markers, microbiota alterations, and sleep parameters. Results: Patients with CRE infections exhibited marked systemic inflammation, reflected by elevated C-reactive protein and altered liver enzyme levels. Significant shifts in oral microbial diversity were observed, with an increased abundance of opportunistic pathogens. Sleep disturbances were common among CRE-infected patients and showed positive correlations with inflammatory markers and oral dysbiosis indices. Multivariate analysis indicated that biochemical abnormalities and microbial imbalance were independent predictors of poor sleep quality. Conclusion: CRE infections are associated with distinct clinicopathological and biochemical profiles, accompanied by significant alterations in oral microbiota and increased prevalence of sleep disorders. These findings highlight the potential bidirectional link between systemic infection, microbial ecology, and sleep regulation, underscoring the need for integrated management strategies in hospitalized patients.